Mixed multifractal analysis of China and US stock index series. (June 2016) - Dai, Meifeng; Hou, Jie; Gao, Jianyu; Su, Weiyi; Xi, Lifeng; Ye, Dandan
Abstract: In this paper, we study mixed multifractal properties of stock index series both in China i.e., SSEC, SZSE and US i, e., DJIA, NASDAQ by mixed multifractal analysis and exploit the inner relationship between them. Further more, we study the relationship between Chinese stock indices and US stock indices in different time period. The results show that there is a higher level of mixed multifractal between SSEC and SZSE, and a lower level between China stock indices and NASDAQ. On the contrary, China stock indices has the highest level with DJIA which means that DJIA not only relates to US stock market, but also affects China stock markets.